ORGANIZATION AND METHODS OF RESEARCH OF PEDAGOGICAL CONDITIONS EFFECTIVENESS OF FORMATION OF FUTURE PILOTS’ COMMUNICATIVE SKILLS - Бородова, О. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article presents the characteristics of organization and methods of research of pedagogical conditions effectiveness of formation of future pilots’ communicative skills. The author reveals the task and substantiates the stages of the pedagogical experiment, and also presents the methods that were used during it. In order to compare the results of the forming experiment, the author formed equivalent groups (control and experimental) according to the following indicators: communicative skills; successfulness in the professionally-oriented disciplines; intelligence; concentration of attention; logical thinking; short - term memory. The results of the forming experiment are presented in the form of tables and figures with the distribution of levels and the Student’s t statistics